Accessing Northern Ireland's contested past: Creating descriptive guides of the Maze and Long Kesh prison video tours - McDonagh, Sarah (The Journal of Specialised Translation, 2023)
This article charts the creation of descriptive guides of a series of video tours of the defunct Maze and Long Kesh prison in Northern Ireland, as part of a PhD research project, in collaboration with the creative team behind the Prisons Memory Archive (PMA) (n.d.), an audiovisual archive that documents the carceral system in Northern Ireland during the 30-year conflict known as 'the Troubles'. In an effort to bridge what Greco has called the "maker-expert-user gap" (2018: 219), a purposeful collaborative methodological approach was applied that involved the author and the PMA creative team alongside PMA participants as well as blind, partially blind and non-blind audiences across the region. In line with recent research on media accessibility, this article foregrounds the broader benefits of an inclusive approach that engages creators and end users in the co-design of accessible content. Drawing on conversations with the PMA creative team and PMA participants as well as the results of an exploratory study with blind, partially blind and non-blind audiences, this article highlights the wider applicability of audio description in engaging people of all abilities with an important, albeit contested, heritage site in Northern Ireland.